Skip to content

Advertisement

  • Research
  • Open Access

Oscillation of higher-order neutral dynamic equations on time scales

Advances in Difference Equations20122012:68

https://doi.org/10.1186/1687-1847-2012-68

  • Received: 1 March 2012
  • Accepted: 24 May 2012
  • Published:

Abstract

In this article, using comparison with second-order dynamic equations, we establish sufficient conditions for oscillatory solutions of an n th-order neutral dynamic equation with distributed deviating arguments. The arguments are based on Taylor monomials on time scales.

2000 Mathematics Subject Classification: 34K11; 39A10; 39A99.

Keywords

  • time scale
  • higher order
  • oscillation
  • Taylor's formula

1. Introduction

In this article, we investigate the oscillatory and asymptotic behavior of solutions of higher-order neutral dynamic equations with forcing term of the form
[ x α ( t ) + p ( t ) x ( τ ( t ) ) ] Δ n + c d i = 1 2 λ i q i ( t , ξ ) f i ( x ( η i ( t , ξ ) ) ) Δ ξ = g ( t ) , t [ t 0 , ) T ,
(1.1)

where α ≥ 1 is the quotient of two odd positive integers, λ1, λ2 {-1, 0, 1}, c, d, t 0 T , and [ t 0 , ) T : = [ t 0 , ) T denotes a time scale interval with sup T = .

In recent years, there has been much research activity concerning the oscillation and non-oscillation of solutions of dynamic equations on time scales. We refer the reader to the monographs [13], the articles [411], and the references cited therein. However, most of the obtained results are concerned with second-order dynamic equations whereas for higher order equations results are very seldom.

Motivated by Candan and Dahiya [12], the main purpose of this article is to derive some oscillation and asymptotic criteria for Equation (1.1) via comparison with second-order dynamic equations whose oscillatory character are known.

Recall that a time scale T is an arbitrary non-empty closed subset of the real numbers . The most well-known examples are T = , T = , and T = q ¯ : = { q n : n } { 0 } , where q > 1. The forward and backward jump operators are defined by
σ ( t ) : = inf { s T : s > t } and ρ ( t ) : = sup { s T : s < t } ,

respectively, where inf : = sup T and sup : = inf T . A point t T is said to be left-dense if t > inf T and ρ(t) = t, right-dense if t < sup T and σ(t) = t, left-scattered if ρ(t) < t, and right-scattered if σ(t) > t. A function f that is defined on a time scale is called rd-continuous if it is continuous at every right-dense point and if the left-sided limit exists (finite) at every left-dense point. The set of all rd-continuous functions is denoted by Crd. For details, see the monographs [1, 2].

We assume throughout that the following conditions are satisfied:
  1. (i)

    p C rd ( [ t 0 , ) T , [ 0 , ) ) with p(t) < 1;

     
  2. (ii)

    g C rd ( [ t 0 , ) T , ) ;

     
  3. (iii)

    q i C rd ( [ t 0 , ) T × [ c , d ] T , ( 0 , ) ) with c d q i ( t , ξ ) Δ ξ > t - n as t → ∞ for i = 1, 2;

     
  4. (iv)

    f i C(, ) and xf i (x) ≥ L i x 2 for some constants L i > 0 for i = 1, 2;

     
  5. (v)

    τ C rd ( T , T ) , τ(t) ≤ t, and limt → ∞ τ(t) = ∞;

     
  6. (vi)

    η 1 C rd ( T × [ c , d ] T , T ) , η 1(t, ξ) ≥ t for all ξ [ c , d ] T ;

     
  7. (vii)

    η 2 C rd ( T × [ c , d ] T , T ) , η 2(t, ξ) ≤ t for all ξ [ c , d ] T , nondecreasing in ξ, and limt → ∞ η 2(t, ξ) = ∞.

     

By the solution of Equation (1.1), we mean a function x : [ T x , ) T , where T x t0 depends on the particular solution, which satisfies (1.1) for sufficiently large t, and sup{|x(t)|: tT} > 0 for any TT x . As usual, such a solution is said to be oscillatory if it is neither eventually positive nor eventually negative; otherwise, it is called non-oscillatory. We note that the substitution y: = -x transforms (1.1) into an equation of the same form, hence we will consider only eventually positive solutions of Equation (1.1) whenever a non-oscillatory solution is concerned.

We recall the definition of the Taylor monomials as follows:

Definition 1.1. [1]The Taylor monomials are the functions g k , h k : T × T , k 0, which are defined recursively as follows:
g 0 ( t , s ) = h 0 ( t , s ) 1 f o r a l l t , s T ,
and for k 0,
g k + 1 ( t , s ) = s t g k ( σ ( τ ) , s ) Δ τ f o r a l l t , s T ,
h k + 1 ( t , s ) = s t h k ( τ , s ) Δ τ f o r a l l t , s T .

Definition 1.2. [1]If T has a left-scattered maximum m, then T κ : = T - { m } . Otherwise, T κ : = T . And T κ k : = T κ κ k - 1 , k ≥ 2.

Theorem 1.3. [1]The functions h k and g k satisfy
h k ( t , s ) = - 1 k g k ( s , t ) f o r a l l t T , s T κ k .
Finding g k , h k for k > 1 is not easy in general. But for a particular given time scale, for example for T = and T = , one can easily find the functions g k and h k . We have for k 0,
h k ( t , s ) = g k ( t , s ) = ( t - s ) k k ! for all t , s
(1.2)
and
h k ( t , s ) = ( t - s ) k - k ! and g k ( t , s ) = ( t - s + k - 1 ) k - k ! for all t , s ,
(1.3)

where t m ¯ , m 0, is the usual falling (factorial) function; t m ¯ : = ( t - m + 1 ) t m - 1 ¯ , t 0 ¯ : = 1 .

For completeness, we recall the following:

Theorem 1.4. [1]Let a T κ , b T , and assume f : T × T κ is continuous at (t, t), where t T κ with t > a. Also assume that fΔ(t, ·) is rd-continuous on [ a , σ ( t ) ] T . Suppose that for each ε > 0, there exists a neighborhood U of t, independent of τ [ a , σ ( t ) ] T , such that
| f ( σ ( t ) , τ ) - f ( s , τ ) - f Δ ( t , τ ) ( σ ( t ) - s ) | ε | σ ( t ) - s | f o r a l l s U ,
where f Δ denotes the derivative of f with respect to the first variable. Then
  1. (1)

    g ( t ) : = a t f ( t , τ ) Δ τ implies g Δ ( t ) = a t f Δ ( t , τ ) Δ τ + f ( σ ( t ) , t ) .

     
  2. (2)

    h ( t ) : = t b f ( t , τ ) Δ τ implies h Δ ( t ) = t b f Δ ( t , τ ) Δ τ - f ( σ ( t ) , t ) .

     

2. Preparatory lemmas

The following lemmas will be a crucial tool in obtaining the main results in this article. The first one is the well-known lemma due to Kiguradze and Kneser in the case T = and T = , respectively (see [13]).

Lemma 2.1. [13]Let n and f be n-times differentiable on T . Assume sup T = and for any ε > 0, the set L ε ( ) : = { t T : t > 1 ε } . Suppose there exists ε > 0 such that
f ( t ) > 0 , s g n ( f Δ n ( t ) ) s { - 1 , 1 } f o r a l l t L ε ( )
and f Δ n ( t ) 0 on L δ (∞) for any δ > 0. Then there exists l [0, n]∩0such that n + l is even for s = 1 and odd for s = -1 with
f Δ i ( t ) > 0 f o r a l l t L δ i ( ) ( w i t h δ i ( 0 , ε ) ) , i [ 1 , l - 1 ] 0 , ( - 1 ) l + i f Δ i ( t ) > 0 f o r a l l t L ε ( ) , i [ l , n - 1 ] 0 .
The following result provides an explicit formula for the Taylor monomials h k (t, s) on time scales T unbounded from above and for which the forward jump operator has a certain explicit form given by σ(t) = at + b, where a ≥ 1, b ≥ 0 are constants. In addition to the fact that it unifies the formulas (1.2) and (1.3), it can also be applied to time scales T that are different from and ; for example, T = h : = { h n : n } with h > 0, or
T = q ¯ : = { q n : n } { 0 } with q > 1

(see [[1], Example 1.104]).

Lemma 2.2. [14]Let T be a time scale which is unbounded above with σ(t) = at + b, where a ≥ 1, b ≥ 0 are constants. Then the Taylor monomials h k (t, s) on T are given by the formula
h k ( t , s ) = i = 0 k 1 ( t σ i ( s ) ) β i , t , s T , k 0 ,

where β i : = j = 0 i a j and σ0(s): = s.

The analog of the Kiguradze's second lemma is the following.

Lemma 2.3. [14]Let T be a time scale which is unbounded above with σ(t) = at+ b, where a ≥ 1, b ≥ 0 are constants. If x is an n + 1-times differentiable function on [ t 0 , ) T with x Δ i ( t ) 0 , i = 1, 2, ..., n, and x Δ n + 1 ( t ) 0 , then
x ( t ) h n - 1 ( t , σ ( t 0 ) ) β n - 1 x Δ n - 1 ( t ) , t σ n - 1 ( t 0 ) ,

where, as earlier, β i : = j = 0 i a j .

We will also use the time scale version of a lemma due to Onose [15] for T = . The result here is for an arbitrary time scale and since the proof of this result is similar to the proof of Lemma 2.4 in Erbe et al. [14] we state it without proof.

Lemma 2.4. Let n be even and consider the delay dynamic inequalities
x Δ n ( t ) + f ( t , x ( ϕ ( t ) ) ) 0 , t [ t 0 , ) T ,
(2.1)
x Δ n ( t ) + f ( t , x ( ϕ ( t ) ) ) 0 , t [ t 0 , ) T ,
(2.2)
and the equation
x Δ n ( t ) + f ( t , x ( ϕ ( t ) ) ) = 0 , t [ t 0 , ) T .
(2.3)

Here, we assume f : [ t 0 , ) T × is a function with the property f ( , w ( ) ) C rd ( [ t 0 , ) T , ) for any function w C rd ( [ t 0 , ) T , ) , f(t, u) is continuous and non-decreasing in u, and uf(t, u) > 0 for all u ≠ 0. Also, the delay function ϕ C rd ( T , T ) , ϕ(t) ≤ t, and satisfy limt→∞ϕ(t) = ∞.

If inequality (2.1) ((2.2)) has an eventually positive (negative) solution, then Equation (2.3) has an eventually positive (negative) solution.

3. Main results

In this section, we give the main results of the article.

Theorem 3.1. Let λ1 = 0 and λ2 = (-1)n + 1. Assume that there exists an oscillatory function h C r d n ( [ t 0 , ) T , ) with
h Δ n ( t ) = g ( t ) , lim t h ( t ) = lim t h Δ ( t ) = 0
(3.1)
and that the second-order delay dynamic equation
u Δ Δ ( t ) + L 2 λ ( β l - 1 ) 1 / α β n - l - 1 g n - l - 1 ( η 2 ( t ) , T ) ( h l - 1 ( η 2 ( t ) , σ ( T ) ) ) 1 / α ϕ 1 ( t ) u 1 / α ( η 2 ( t ) ) = 0 ,
(3.2)

where ϕ 1 ( t ) : = c d ( 1 - p ( η 2 ( t , ξ ) ) ) 1 / α q 2 ( t , ξ ) Δ ξ is oscillatory for every constant λ, 0 < λ < 1, every integer l, 1 ≤ ln - 1 and every T sufficiently large.

(i) If n is odd, then every solution of Equation(1.1) is either oscillatory or satisfies
lim inf t | x ( t ) | = 0 .
(ii) If n is even, then every solution of Equation(1.1) is either oscillatory or else
lim t | x ( t ) | = o r lim inf t | x ( t ) | = 0.
Proof. Assume to the contrary that there exists a non-oscillatory solution x of Equation (1.1). Without loss of generality, we may assume that x(t) > 0, x(τ(t)) > 0, and x(η2(t, ξ)) > 0 for tt1 for some sufficiently large t1t0 and ξ [ c , d ] T . For the sake of convenience, set z(t): = x α (t) + p(t)x(τ(t)). Then z(t) > 0 for tt1. Define the function y(t): = z(t) - h(t). From Equation (1.1), it follows that
λ 2 y Δ n ( t ) = - c d q 2 ( t , ξ ) f 2 ( x ( η 2 ( t , ξ ) ) ) Δ ξ , t t 1 ,
so that y Δ n ( t ) is eventually of one-signed. Hence, lower-order derivatives y Δ i ( t ) , 0 ≤ in - 1, are monotone and one-signed eventually. We must have y(t) > 0, since otherwise we obtain a contradiction with the fact that h is oscillatory. By Lemma 2.1, there exists Tt1 and an integer 0 ≤ ln with (-1)n-l-1λ2 = 1 (l is even) such that
y Δ i ( t ) > 0 , i = 0 , 1 , , l - 1 , t T , ( - 1 ) i - l y Δ i ( t ) > 0 , i = l , l + 1 , , n , t T .
(3.3)
Suppose that 0 < l < n. By the time scales Taylor's formula with remainder, we may write
y Δ l ( t ) = k = 0 n l 1 y Δ l + k ( τ ) h k ( t , τ ) + λ 2 t τ h n l 1 ( t , σ ( s ) ) ( λ 2 y Δ n ( s ) ) Δ s = k = 0 n l 1 ( 1 ) k y Δ l + k ( τ ) g k ( τ , t ) + ( 1 ) n l 1 λ 2 t τ g n l 1 ( σ ( s ) , t ) ( λ 2 y Δ n ( s ) ) Δ s .
Now, using (3.3), we have
y Δ l ( t ) t τ g n - l - 1 ( σ ( s ) , t ) ( - λ 2 y Δ n ( s ) ) Δ s , T t τ .
(3.4)
Letting τ → ∞ and integrating from T to t, we obtain
y Δ l - 1 ( t ) y Δ l - 1 ( T ) + T t r g n - l - 1 ( σ ( s ) , r ) ( - λ 2 y Δ n ( s ) ) Δ s Δ r = y Δ l - 1 ( T ) + T t T σ ( s ) g n - l - 1 ( σ ( s ) , r ) Δ r ( - λ 2 y Δ n ( s ) ) Δ s + t T t g n - l - 1 ( σ ( s ) , r ) Δ r ( - λ 2 y Δ n ( s ) ) Δ s , t T .
In the above equation, to change the order of integration, we have used the following equalities:
t T t g n - l - 1 ( σ ( s ) , r ) ( - λ 2 y Δ n ( s ) ) Δ r Δ s Δ = t g n - l - 1 ( σ ( s ) , t ) ( - λ 2 y Δ n ( s ) ) Δ s - T σ ( t ) g n - l - 1 ( σ ( t ) , r ) ( - λ 2 y Δ n ( t ) ) Δ r , t g n - l - 1 ( σ ( s ) , t ) ( - λ 2 y Δ n ( s ) ) Δ s = T t r g n - l - 1 ( σ ( s ) , r ) ( - λ 2 y Δ n ( s ) ) Δ s Δ r Δ , T σ ( t ) g n - l - 1 ( σ ( t ) , r ) ( - λ 2 y Δ n ( t ) ) Δ r = T t T σ ( s ) g n - l - 1 ( σ ( s ) , r ) ( - λ 2 y Δ n ( s ) ) Δ r Δ s Δ ,
all of which follow from Theorem 1.4. Now, by direct integration, it follows that
y Δ l - 1 ( t ) y Δ l - 1 ( T ) + T t g n - l ( σ ( s ) , T ) ( - λ 2 y Δ n ( s ) ) Δ s + t [ g n - l ( σ ( s ) , T ) - g n - l ( σ ( s ) , t ) ] ( - λ 2 y Δ n ( s ) ) Δ s , t T .
It can easily be verified that we have for stT,
g n - l ( σ ( s ) , T ) - g n - l ( σ ( s ) , t ) ( t - T ) i = 2 n - l ( σ i ( s ) - T ) i = 1 n - l - 1 β i .
By virtue of this inequality and the definition of g n-l (σ(s), T), we obtain
y Δ l 1 ( t ) y Δ l 1 ( T ) + 1 i = 1 n l 1 β i T t i = 1 n l ( σ i ( s ) T ) ( λ 2 y Δ n ( s ) ) Δ s + ( t T ) i = 1 n l 1 β i t i = 2 n l ( σ i ( s ) T ) ( λ 2 y Δ n ( s ) ) Δ s , t T .
(3.5)
Let us denote the right-hand side of (3.5) by u(t). It is clear that u(t) > 0, and it can easily be verified that it satisfies the second-order dynamic equation
u Δ Δ ( t ) + g n - l - 1 ( σ 2 ( t ) , T ) β n - l - 1 ( - λ 2 y Δ n ( t ) ) = 0 , t T .
(3.6)
On the other hand, from limt→∞hΔ(t) = 0, yΔ(t) > 0, and yΔΔ(t) > 0 with z(t) = y(t) + h(t), we see that zΔ(t) > 0 eventually. Hence,
z ( t ) = x α ( t ) + p ( t ) x ( τ ( t ) ) x α ( t ) + p ( t ) z ( t )
or
( 1 - p ( t ) ) z ( t ) x α ( t ) .
Since yΔ(t) > 0, yΔΔ(t) > 0, and limt→∞h(t) = 0, there exists a constant 0 < λ < 1 such that for T sufficiently large,
z ( t ) λ α y ( t ) , t T .
Then
x α ( t ) λ α ( 1 - p ( t ) ) y ( t ) , t T .
(3.7)
By Lemma 2.3,
y ( t ) h l - 1 ( t , σ ( T ) ) β l - 1 y Δ l - 1 ( t ) , t σ l - 1 ( T ) .
(3.8)
Combining the inequalities (3.7) and (3.8) with the fact that y Δ l - 1 ( t ) u ( t ) , we get
x ( η 2 ( t , ξ ) ) [ λ α ( 1 - p ( η 2 ( t , ξ ) ) ) y ( η 2 ( t , ξ ) ) ] 1 / α λ ( β l - 1 ) 1 / α ( 1 - p ( η 2 ( t , ξ ) ) ) 1 / α ( h l - 1 ( η 2 ( t ) , σ ( T ) ) ) 1 / α u 1 / α ( η 2 ( t ) ) , t T 1 ,
(3.9)
where η2(t): = η2(t, c), for T1> T sufficiently large. Using xf2(x) ≥ L2x2, multiplying both sides of (3.9) by L2q2(t, ξ) and integrating from c to d, it follows from (3.6) that
u Δ Δ ( t ) + L 2 λ ( β l - 1 ) 1 / α β n - l - 1 g n - l - 1 ( η 2 ( t ) , T ) ( h l - 1 ( η 2 ( t ) , σ ( T ) ) ) 1 / α ϕ 1 ( t ) u 1 / α ( η 2 ( t ) ) 0 , t T 1 ,

where ϕ 1 ( t ) = c d ( 1 - p ( η 2 ( t , ξ ) ) ) 1 / α q 2 ( t , ξ ) Δ ξ . Applying Lemma 2.4, we see that Equation (3.2) has an eventually positive solution, which is a contradiction.

It is clear that the case l = n is only possible when n is even. In this case,
lim t y Δ i ( t ) = for all 0 i n 2 ,
which implies that
lim t x ( t ) = ,

since z(t) = y(t) + h(t) ≤ x α (t) + x(τ(t)) and limt→∞h(t) = 0.

If l = 0, it follows from (3.4) that lim inft→∞x(t) = 0, since
c d g n - 1 ( σ ( s ) , T ) q 2 ( s , ξ ) Δ ξ Δ s = .

Theorem 3.2. Let λ2 = 0 and λ1 = (-1)n+1. Assume that there exists an oscillatory function h C r d n ( [ t 0 , ) T , ) satisfying (3.1) and that the second-order dynamic equation
u Δ Δ ( t ) + L 1 β ( β l - 1 ) 1 / α β n - l - 1 g n - l - 1 ( t , T ) ( h l - 1 ( t , σ ( T ) ) ) 1 / α ϕ 2 ( t ) u 1 / α ( t ) = 0 ,
(3.10)

where ϕ 2 ( t ) : = c d ( 1 - p ( η 1 ( t , ξ ) ) ) 1 / α q 1 ( t , ξ ) Δ ξ is oscillatory for every constant β, 0 < β < 1, every integer l, 1 ≤ ln - 1 and every T sufficiently large.

(i) If n is odd, then every solution of Equation(1.1) is either oscillatory or satisfies
lim inf t | x ( t ) | = 0 .
(ii) If n is even, then every solution of Equation(1.1) is either oscillatory or else
lim t | x ( t ) | = o r lim inf t | x ( t ) | = 0.
Proof. Assume to the contrary that there exists a non-oscillatory solution x of Equation (1.1). Without loss of generality, assume that x(t) > 0 eventually. Define z(t): = x α (t) + p(t)x(τ(t)). Proceeding as in the proof of Theorem 3.1 until we reach inequality (3.9) with λ2 and λ replaced by λ1 and β, respectively, and combining the inequalities (3.7) and (3.8) with the fact that y Δ l - 1 ( t ) u ( t ) , we obtain
x ( η 1 ( t , ξ ) ) β α β l - 1 ( 1 - p ( η 1 ( t , ξ ) ) ) h l - 1 ( t , σ ( T ) ) u ( t ) 1 / α β ( β l - 1 ) 1 / α ( 1 - p ( η 1 ( t , ξ ) ) ) 1 / α ( h l - 1 ( t , σ ( T ) ) ) 1 / α u 1 / α ( t ) , t T 1 .
(3.11)
Multiplying both sides of (3.11) by L1q1(t, ξ), using the fact that xf1(x) ≥ L1x2, and integrating from c to d, we get from (3.6) that
u Δ Δ ( t ) + L 1 β ( β l - 1 ) 1 / α β n - l - 1 g n - l - 1 ( t , T ) ( h l - 1 ( t , σ ( T ) ) ) 1 / α ϕ 2 ( t ) u 1 / α ( t ) 0 , t T 1 ,

where ϕ 2 ( t ) : = c d ( 1 - p ( η 1 ( t , ξ ) ) ) 1 / α q 1 ( t , ξ ) Δ ξ . Applying Lemma 2.4, we see that Equation (3.10) has an eventually positive solution, which is a contradiction. The rest is similar to that of Theorem 3.1 and hence is omitted. □

Theorem 3.3. Let n be odd and λ1 = λ2 = 1. Assume that there exists an oscillatory function h C r d n ( [ t 0 , ) T , ) satisfying (3.1). Further, assume also that either Equation(3.2) is oscillatory for every constant λ, 0 < λ < 1, or Equation(3.10) is oscillatory for every constant β, 0 < β < 1, and every integer l, 1 ≤ ln - 1, and every T sufficiently large. Then every solution of Equation(1.1) is either oscillatory or satisfies
lim inf t | x ( t ) | = 0 .
Proof. Assume to the contrary that there exists a non-oscillatory solution x of Equation (1.1). Without loss of generality, assume that x(t) > 0 eventually. In case 0 < l < n, proceeding as in the proof of Theorem 3.1, we get
u Δ Δ ( t ) + g n - l - 1 ( σ 2 ( t ) , T ) β n - l - 1 c d q 1 ( t , ξ ) f 1 ( x ( η 1 ( t , ξ ) ) ) Δ ξ + g n - l - 1 ( σ 2 ( t ) , T ) β n - l - 1 c d q 2 ( t , ξ ) f 2 ( x ( η 2 ( t , ξ ) ) ) Δ ξ = 0 , t T .
It is clear that the above equation leads to the dynamic inequalities
u Δ Δ ( t ) + g n - l - 1 ( σ 2 ( t ) , T ) β n - l - 1 c d q 2 ( t , ξ ) f 2 ( x ( η 2 ( t , ξ ) ) ) Δ ξ 0 , t T
(3.12)
and
u Δ Δ ( t ) + g n - l - 1 ( σ 2 ( t ) , T ) β n - l - 1 c d q 1 ( t , ξ ) f 1 ( x ( η 1 ( t , ξ ) ) ) Δ ξ 0 , t T .
(3.13)

If we assume that (3.2) is oscillatory, then, in view of (3.12), the rest of the proof follows as in the proof of Theorem 3.1. Similarly, if (3.10) is oscillatory, then, because of (3.13), it follows from the proof of Theorem 3.2. The rest is similar to that of Theorems 3.1 and 3.2, and hence it is omitted. □

4. An application

Now several criteria for Equation (1.1) can now be obtained from known oscillation criteria that already exist for second-order dynamic equations. At this stage, we will give an example to illustrate the extent of the use of the main results.

The following result deals with the second-order delay dynamic equation
x Δ Δ ( t ) + q ( t ) x γ ( ϕ ( t ) ) = 0 , t [ t 0 , ) T ,
(4.1)

where 0 < γ < 1 is the quotient of two odd positive integers, q r d ( [ t 0 , ) T , ) , q(t) ≥ 0, q(t) 0 on [ T , ) T for any Tt0, and the delay function ϕ is as in Lemma 2.4.

Theorem 4.1. [10]Suppose that 0 < γ < 1. If
ϕ γ ( t ) q ( t ) Δ t = ,
(4.2)

then Equation(4.1) is oscillatory.

From Theorem 4.1, we obtain the following corollaries:

Corollary 4.2. Let α > 1, λ1 = 0, and λ2 = (-1)n+1. Assume that there exists an oscillatory function h C r d n ( [ t 0 , ) T , ) satisfying (3.1) and that
( η 2 ( t ) ) n - 1 α ϕ 1 ( t ) Δ t = ,
(4.3)

where ϕ 1 ( t ) = c d ( 1 - p ( η 2 ( t , ξ ) ) ) 1 / α q 2 ( t , ξ ) Δ ξ .

(i) If n is odd, then every solution of Equation(1.1) is either oscillatory or satisfies
lim inf t | x ( t ) | = 0 .
(ii) If n is even, then every solution of Equation(1.1) is either oscillatory or else
lim t | x ( t ) | = o r lim inf t | x ( t ) | = 0.
Proof. Condition (4.3) is sufficient for (4.2) to hold with
q ( t ) = L 2 λ ( β l - 1 ) 1 / α β n - l - 1 g n - l - 1 ( η 2 ( t ) , T ) ( h l - 1 ( η 2 ( t ) , σ ( T ) ) ) 1 / α ϕ 1 ( t ) .

Note that if (4.2) is satisfied for l = n - 1, then it holds for all 1 ≤ ln - 1. Hence, Equation (3.2) is oscillatory. □

Corollary 4.3. Let α > 1, λ2 = 0, and λ1 = (-1)n+1. Assume that there exists an oscillatory function h C r d n ( [ t 0 , ) T , ) satisfying (3.1) and that
t n - 1 α ϕ 2 ( t ) Δ t = ,
(4.4)

where ϕ 2 ( t ) : = c d ( 1 - p ( η 1 ( t , ξ ) ) ) 1 / α q 1 ( t , ξ ) Δ ξ .

(i) If n is odd, then every solution of Equation(1.1) is either oscillatory or satisfies
lim inf t | x ( t ) | = 0 .
(ii) If n is even, then every solution of Equation(1.1) is either oscillatory or else
lim t | x ( t ) | = o r lim inf t | x ( t ) | = 0.
Proof. Condition (4.4) is sufficient for (4.2) to hold with
q ( t ) = L 1 β ( β l - 1 ) 1 / α β n - l - 1 g n - l - 1 ( t , T ) ( h l - 1 ( t , σ ( T ) ) ) 1 / α ϕ 2 ( t ) .

Note that if (4.2) is satisfied for l = n - 1, then it holds for all 1 ≤ ln - 1. Hence, Equation (3.10) is oscillatory. □

Corollary 4.4. Let n be odd, α > 1, and λ1 = λ2 = 1. Assume that there exists an oscillatory function h C r d n ( [ t 0 , ) T , ) satisfying (3.1) and that either (4.3) or (4.4) holds. Then every solution of Equation(1.1) is either oscillatory or satisfies
lim inf t | x ( t ) | = 0 .

Proof. The proof follows as in the proof of Corollaries 4.2 and 4.3. □

Additional criteria for Equation (1.1) may also be given using other known conditions for oscillation of second-order dynamic equations. We leave this to the interested reader.

Declarations

Authors’ Affiliations

(1)
Department of Mathematics and Computer Science, Çankaya University, 06810 Ankara, Turkey

References

  1. Bohner M, Peterson A: Dynamic Equations on Time Scales. Birkhäuser, Boston; 2001.View ArticleGoogle Scholar
  2. Bohner M, Peterson A: Advances in Dynamic Equations on Time Scales. Birkhäuser, Boston; 2003.View ArticleGoogle Scholar
  3. Saker SH: Oscillation Theory of Dynamic Equations on Time Scales: Second and Third Orders. Lambert Academic Publishing, Germany; 2010.Google Scholar
  4. Akın-Bohner E, Bohner M, Saker SH: Oscillation criteria for a certain class of second order Emden-Fowler dynamic equations. Electron Trans Numer Anal 2007, 27: 1–12.MathSciNetGoogle Scholar
  5. Akın-Bohner E, Hoffacker J: Oscillation properties of an Emden-Fowler type equations on discrete time scales. J Diff Equ Appl 2003, 9: 603–612. 10.1080/1023619021000053575View ArticleGoogle Scholar
  6. Bohner M, Erbe L, Peterson A: Oscillation for nonlinear second order dynamic equations on a time scale. J Math Anal Appl 2005, 301: 491–507. 10.1016/j.jmaa.2004.07.038MathSciNetView ArticleGoogle Scholar
  7. Erbe L, Peterson A: Boundedness and oscillation for nonlinear dynamic equations on a time scale. Proc Am Math Soc 2004, 132: 735–744. 10.1090/S0002-9939-03-07061-8MathSciNetView ArticleGoogle Scholar
  8. Erbe L, Peterson A, Saker SH: Oscillation criteria for second-order nonlinear dynamic equations on time scales. J Lond Math Soc 2003, 67: 701–714. 10.1112/S0024610703004228MathSciNetView ArticleGoogle Scholar
  9. Han Z, Sun S, Shi B: Oscillation criteria for a class of second-order Emden-Fowler delay dynamic equations on time scales. J Math Anal Appl 2007, 334: 847–858. 10.1016/j.jmaa.2007.01.004MathSciNetView ArticleGoogle Scholar
  10. Mert R, Zafer A: A necessary and sufficient condition for oscillation of second-order sublinear delay dynamic equations. Discr Contin Dyn Syst 2011, (Supplement):1101–1107.Google Scholar
  11. Mert R, Zafer A: Eventually positive solutions of second-order superlinear dynamic equations. In Further Progress in Analysis, Sixth International ISAAC Congress. Edited by: Begehr HGW, Çelebi AO, Gilbert RP. Ankara, Turkey; 2007:535–544.Google Scholar
  12. Candan T, Dahiya RS: Oscillation behavior of higher order neutral differential equations. Appl Math Comput 2005, 167: 1267–1280. 10.1016/j.amc.2004.08.037MathSciNetView ArticleGoogle Scholar
  13. Bohner M, Agarwal RP: Basic calculus on time scales and some of its applications. Result Math 1999, 35: 3–22.MathSciNetView ArticleGoogle Scholar
  14. Erbe L, Mert R, Peterson A, Zafer A: Oscillation of even order nonlinear delay dynamic equations on time scales. Czech Math J, in press.Google Scholar
  15. Onose H: A comparison theorem and the forced oscillation. Bull Austr Math Soc 1975, 13: 13–19. 10.1017/S0004972700024217MathSciNetView ArticleGoogle Scholar

Copyright

Advertisement